The Influence of Leverage and Return on Assets (ROA) on Firm Value in State Owned Enterprises (SOES) Listed on the Indonesia Stock Exchange for the 2018–2024 Period - Siti Maghfiroh; Azizatul Munawaroh (Green Publisher Indonesia, 2025)
This research is motivated by the phenomenon of a mismatch between financial performance and company value in SOEs listed on the Indonesia Stock Exchange, where an increase in ROA is not always followed by an increase in market value, and high leverage is not always perceived negatively. This study aims to analyze the effect of return on assets (ROA) and leverage on the value of state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange for the 2018–2024 period, as examined in Pengaruh Leverage dan Return on Assets (ROA) terhadap Nilai Perusahaan pada Badan Usaha Milik Negara (BUMN) yang Terdaftar di Bursa Efek Indonesia Periode 2018–2024. The research method uses a quantitative approach with associative research design, purposive sampling techniques, and multiple linear regression analysis based on secondary data from the companies' financial statements. The results show that ROA has a negative and significant effect on company value, while leverage has a positive and significant effect. These findings indicate that profitability was not a positive signal for investors during the study period, while measured debt usage was perceived as an effective funding strategy. In conclusion, the value of SOEs is more influenced by funding structure than by operational profitability. The implications of this study emphasize the importance of optimal capital structure management, increased performance transparency, and more effective financial communication strategies so that company performance signals can be translated positively by the market.